2012
DOI: 10.1029/2011jf002329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of river regulation on aeolian landscapes, Colorado River, southwestern USA

Abstract: [1] Connectivity between fluvial and aeolian sedimentary systems plays an important role in the physical and biological environment of dryland regions. This study examines the coupling between fluvial sand deposits and aeolian dune fields in bedrock canyons of the arid to semiarid Colorado River corridor, southwestern USA. By quantifying significant differences between aeolian landscapes with and without modern fluvial sediment sources, this work demonstrates for the first time that the flow-and sediment-limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
104
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 207 publications
(246 reference statements)
2
104
0
Order By: Relevance
“…The 2008 weather station data showed that although the flood-formed sandbar riverward (southwest) of the study sites was enlarged substantially during the 2008 HFE, the dominant wind direction did not move sand from the sandbar into the dune field (Draut and others, 2009b). The dominant wind direction in 2008 was similar to conditions measured in previous years (Draut and Rubin, 2008;Draut andothers, 2009a, 2009b).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…The 2008 weather station data showed that although the flood-formed sandbar riverward (southwest) of the study sites was enlarged substantially during the 2008 HFE, the dominant wind direction did not move sand from the sandbar into the dune field (Draut and others, 2009b). The dominant wind direction in 2008 was similar to conditions measured in previous years (Draut and Rubin, 2008;Draut andothers, 2009a, 2009b).…”
Section: Introductionsupporting
confidence: 68%
“…Although gully erosion is not a recent phenomenon in the Grand Canyon, gully erosion in the pre-dam era was partially offset by fine-sediment redistribution into gullies during annual spring runoff floods and migration of aeolian dunes into gully areas (McKee, 1938;Hereford and others, 1993;Sankey and Draut, 2014). In the post-dam era, the sediment load and magnitude of floods have been greatly reduced (Topping and others, 2003), along with the redistribution of flood sands by wind (Draut and Rubin, 2008;Draut, 2012); the degree to which these changes affect the preservation of irreplaceable archaeological resources in the Grand Canyon is a subject of on-going investigations (for example, others, 2009, 2012;Fairley and others, 2012;Sankey and Draut, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis posits that the reduction in the number and areal extent of high-elevation sand bars (Schmidt and others, 2004;Hazel and others, 2010;Schmidt and Grams, 2011a) has resulted in a reduction in the amount of sand available to be transported inland towards archeological sites by wind; this, in turn, has changed the depth and surface characteristics of aeolian sand cover at many archeological sites (Lucchitta, 1991;Thompson and Potochnik, 2000;Draut and Rubin, 2008;Draut, 2012). The post-dam decrease in large, unvegetated sandbars is therefore hypothesized to have resulted in a consequent increase in the amount and intensity of surface erosion at archeological sites due to a decrease in sand transport to the sites.…”
Section: Introductionmentioning
confidence: 99%
“…In 1963, with completion of Glen Canyon Dam 25 km upstream of the Grand Canyon, the Colorado River's natural hydrology was radically altered (Topping and others, 2003), with concomitant landscape effects and ecological consequences (U.S. Department of the Interior, 1995). These consequences include a reduction in the size and volume of sand bars (Schmidt and others, 2004;Hazel and others, 2010), an increase in riparian vegetation at low elevations and senescence of the riparian vegetation at higher elevations (Turner and Karpiscak, 1980;Waring, 1996), reduction in the amount of active aeolian sand dune areas (Draut, 2012), and lack of new sediment deposition by floods above the 1,274 m 3 /s (45,000 cubic feet per second, ft 3 /s) stage within the river corridor (Melis, 2011). In combination, these changes appear to have resulted in an increase in gully erosion and gradual exposure of buried archeological sites situated in and on the pre-dam alluvial terraces above the level of the active river channel (Fairley, 2005;Fairley and Sondossi, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation